ETHNO CULTURAL MEASUREMENT OF MODERN CIVILIZATION'S VECTORS "EAST-WEST", "SOUTH-NORTH" - Харченко, С. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article, the socio-philosophic analisis of the specific of ethno cultural vectors "East-West", "South-North" is carried out.